Writing on the Edge: A Strategic Map of Contemporary Ukrainian Dramaturgy - Bondareva, Olena; Shtepenko, Oleksandra (Theoria et Historia Scientiarum, 2025)
This article presents a large array of fictional texts about the war created by Ukrainian playwrights in 2022 and 2023. The study pays due attention to the strategies of playwriting catalyzed by a full-scale war: the formation of combatant drama, the creation of the unifying map of Ukraine through cataloging its topoi, the designation of new places of power, the movement of the previously peripheral discourses of the dramatic world picture towards the center. Ultimately, the study looks at interesting unifying initiatives and a collective dramatic text about the war differently interpreted in the published drama anthologies: The Unnamed War, Anthology 24, Drama Panorama 2023, and This Day Lasts an Eternity.